Reliability analisis of examination questions in a mathematics course using rasch measurement model - Zulkifli Mohd Nopiah,; Mohd Helmi Jamaluddin,; Nur Arzilah Ismail,; Haliza Othman,; Izamarlina Asshaari,; Mohd Hanif Osman, (Universiti Kebangsaan Malaysia, 2012)
Students’ performance cannot be based solely on their ability to answer questions. The accuracy of the exam questions must also be considered when measuring the outcome of the course. The objective of this paper was to study the reliability of a question and its impact on students’ performance. A well-constructed question should be commensurate with the level of the intended knowledge. In this study, results from a linear algebra examination were analysed using the Rasch Model. The Rasch Model was used to analyse the reliability, non-redundancy and suitability of exam questions. The results showed that, in this particular case, the linear algebra questions were correctly constructed without any redundancy and suitable for the intended students.